Best Practices of a School-based Pre-service Teacher Education Programme - Sharma, Poonam (Voices of Teachers and Teacher Educators, 2022)
This paper reports the documentation of best practices from the case study of a programme run by Muktangan Education Trust, a Mumbai-based NGO. First, the article enlists the core practices of the programme that were valued by the key stakeholders, including teacher educators, teacher trainees and the school management. It illustrates how these practices were spread across the three years. These practices are deliberated upon in the light of literature that vouches for more practice-based teacher education that gives teachers early exposure to school cultures while simultaneously learning from theoretical inputs as well as personal experience. The paper then accounts for some of the challenges faced by teacher education programmes.